2020
DOI: 10.3389/fonc.2019.01362
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient for Distinguishing Between Malignant and Benign Lesions in the Head and Neck Region: A Systematic Review and Meta-Analysis

Abstract: Background: The purpose of the present meta-analysis was to provide evident data about use of apparent diffusion coefficient (ADC) values for distinguishing malignant and benign lesions in the head and neck region. Material and Methods: MEDLINE and Scopus databases were screened for associations between ADC and malignancy/benignancy of head and neck lesions up to December 2018. Overall, 22 studies met the inclusion criteria. The following data were extracted: authors, year of publication, study design, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
2
30
0
1
Order By: Relevance
“…In parotid glands, DW-MRI is commonly used in clinical evaluation, for example with information about localization of the tumor within the parotid gland and differentiation of malignancy from benignity (3). It has also been investigated for the diagnosis of xerostomia, Sjögren's syndrome, Kimura disease and other non-neoplastic disorders affecting the parotid glands.…”
Section: Introductionmentioning
confidence: 99%
“…In parotid glands, DW-MRI is commonly used in clinical evaluation, for example with information about localization of the tumor within the parotid gland and differentiation of malignancy from benignity (3). It has also been investigated for the diagnosis of xerostomia, Sjögren's syndrome, Kimura disease and other non-neoplastic disorders affecting the parotid glands.…”
Section: Introductionmentioning
confidence: 99%
“…Suh et al their meta-analysis suggested that the median ADC cutoff value of 0.965 × 10 − 3 mm 2 /s can differentiate between benign and malignant nodes [ 27 ]. Most recent meta-analysis indicates that the studies which previously used DWI/ADC for differentiating benign from malignant nodes reported limited role due to small sample studies, a wide range of ADC threshold values [ 28 ]. The study suggested that it may be only lesions with mean ADC values above 1.75 × 10 − 3 mm 2 /s are probably benign [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely shown that ADC is inversely associated with cell count and proliferation potential throughout oncology [7][8][9]. A key fact is that typically malignant tumors have lower ADC values in comparison to benign ones, which was shown for several body regions [10][11][12].…”
Section: Introductionmentioning
confidence: 91%